Evaluation of a renoprotective potential of organospecific peptides under the conditions of acute kidney injury of different etiology - Shchudrova, T. S.; Zamorskii, I. I.; Korotun, O. P. (Journal of Education, Health and Sport, 2018)
Acute kidney injury (AKI) is a clinical syndrome which incidence increases dramatically over the past years in both developing and developed countries. It is considered as an independent risk factor for mortality in critically ill patients as well as complicates the course of a significant number of diseases. Consequently, there is a great need for new effective renoprotective options. Our research was conducted to evaluate the renoprotective potential of organospecific peptides (peptide kidney complex, synthetic oligopeptides AED, EDL and AEDG) in comparison with antioxidant drug mexidol (emoxypine succinate) and pineal hormone melatonin. An integral criterion of renoprotective activity was a survival rate of animals under the conditions of AKI of different genesis: induced by ethylene glycol, cisplatin, gentamicin, rhabdomyolysis and ischemia-reperfusion. All of the studied peptides decreased mortality of animals, while the most significant protective effect was shown by peptide EDL, confirmed by 33.3% survival rate on the 5th day of ethylene glycol intoxication development and 100% survival on the other models of AKI. The least effective was peptide AED, as it prevented mortality only in animals with cisplatin-induced AKI. Obtained results show the renoprotective potential of organospecific peptides and give the background for their further study.